REVITALISASI PENDIDIKAN AQIDAH AKHLAK DALAM MEMBANGUN IDENTITAS KEISLAMAN SISWA PADA ERA DIGITAL DI MTS TARBIYATUL IHSAN PROBOLINGGO - Puspita, Nur Indah Tri Yanuar; Hidayah, Ulil (Jurnal Manajemen Pendidikan, 2025)
The objective of this study is to explore the implementation and effectiveness of the revitalization of Aqidah Akhlak education in shaping students’ Islamic identity in the digital era at MTs Tarbiyatul Ihsan Probolinggo. The institution faces significant challenges, particularly the declining religious sensitivity and ethical behavior among students, underscoring the urgency of reinforcing moral values within the educational process. This research employed a qualitative descriptive approach, utilizing in-depth interviews, participatory observation, and documentation as data collection techniques. Data analysis was conducted through source triangulation to ensure the validity of findings. The study revealed five key findings: (1) The transformation of teaching methods to adapt to the digital era represents a strategic response to contemporary pedagogical demands; (2) The role of teachers as facilitators and role models, both in physical and digital spaces, constitutes a crucial element in the transmission of values; (3) The integration of Islamic soft skills into the character-building process strengthens students’ spiritual foundations; (4) Systemic and sustainable institutional policies significantly reinforce the implementation of Aqidah Akhlak education; and (5) The formation of Islamic identity through a holistic and integrative approach demonstrates the success of value-based educational revitalization.